TINGKAT KEHADIRAN DAN KENANEKARAGAMN JENIS MAMALIA DI AREAL REKLAMASI PT. BERAU COAL, KALIMANTAN TIMUR (Jurnal Bioconcetta, 2019)
Mining activities have a big impact to change environmental condition and biodiversity. The government, through its rules requires an environmental management process at mining site. PT. Berau Coal has a high commitment in efforts to improve the environment, it's proved by the revegetation and monitoring of reclamation areas that cariied out every year. This research aims to see the diversity of mammals in reclamation area as one indicator of the success of revegetation program carried out by PT. Berau Coal. This research conducted in 3 reclamation areas, Lati Site, Binungan Site, and Sambarata Site. Data that used are biodiversity monitoring from 2014 - 2017.  Some of analyzes used include Biodiversity Index (H') and Equity Index (E). The results showed that the presence of mammal in reclamation area was quite high with an average annual presence of 21 species in Lati Site, 21 species in Binungan Site, and 23 species in Sambarata Site. Whereas if viewed from the annual average number of individuals present were 70 individuals in Lati Site, 56 individuals in Sambarata Site, and 74 jndividuals im Binungan Site. This level of delivery provides a description that the reclamation area of PT. Berau Coal has able provide a good habitat for mammals. While the biodiversity values (H ') of mammals are at Lati 2.45; H 'in Binungan 2.67 and H' in sambarata 2.52